Educator Competency in Prophetic Perspective - Qomarudin, A; Mutholingah, Siti (Proceeding of International Conference on Islamic Education (ICIED), 2019)
In the context of national education, an educator is required to have four competencies, namely: pedagogic, personality, social, and professional. This is regulated in Law Number 14 of 2005 concerning teachers and lecturers, Ministry of Education Regulation Number 16 of 2007 concerning Academic Qualification Standards and Teacher Competence. Islamic education as one part of national education has a role to create educators who have 4 competencies. Research question on this study how is the four competencies of educators in a prophetic perspective? This study aims to analyze the 4 competencies of educators in prophetic perspective. This study use qualitative approach with the type library research. The result of this study, in prophetic perspective, some of the competencies that must be possessed by the educators above, can be juxtaposed with the prophetic qualities inherent in the Prophet. Personality competence can be attributed to shidiq , social competence can be attributed to amanah , pedagogical competence can be attributed to tabligh, and professional competence can be attributed to fathonah. Thus, educators who continue to increase their competence as educators are the same as trying to emulate the attributes of the Prophet